An Evaluation of LGU Personnel Performance and Citizen Satisfaction on Essential Services Delivery in the First-Class Municipality - Alvarado, Randy; Lumbab, Keneth Ray; Bocanegra, Lorenzo; Yaun Jr., Allan; Lauronilla, Abigail Ann (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the relationship between Local Government Unit personnel performance and citizen satisfaction with essential services delivery in the Municipality of Sibonga, Cebu. Specifically, it examined whether department-level Individual Performance Commitment and Review ratings aligned with department-level client satisfaction ratings across Health Services, Social Services, Engineering Services, and Administrative Services. The study was anchored on Goal-Setting Theory and Expectancy-Disconfirmation Theory, which respectively explain internal performance motivation and external citizen satisfaction based on service expectations and actual experiences. A quantitative, cross-sectional, descriptive-correlational design was used. The study utilized secondary department-level administrative data from official personnel performance records and existing service-area client satisfaction databanks covering the same 12-month period. The respondents consisted of 55 LGU personnel from the four focal departments. Data were gathered using the Departmental IPCR Summary Form and the Citizen Satisfaction Data Extraction Sheet. Descriptive statistics were used to summarize personnel profile, departmental performance, and satisfaction levels, while Spearman’s rank-order correlation was used to determine the relationship between personnel performance and client satisfaction. Findings showed that the LGU workforce was mostly composed of mid-career personnel, with the 31–40 and 41–50 age groups each representing 30.9% of the workforce. Gender distribution was nearly balanced, with 50.9% female and 49.1% male personnel. All respondents had graduate-level education, and many had moderate to longer years of government service. All departments obtained “Very Satisfactory” IPCR ratings, with Health Services recording the highest mean rating of 4.2020. Client satisfaction was also rated “Very Satisfactory” across responsiveness, timeliness, accessibility, and outcome. Engineering Services obtained some of the highest satisfaction means, while Administrative Services posted the lowest outcome score of 3.9800, though still within the “Very Satisfactory” range. A strong, positive, and statistically significant relationship was found between IPCR performance ratings and client satisfaction, with Spearman’s rho of .786 and p = .000. The findings indicate that higher internal performance ratings were strongly associated with higher citizen satisfaction. The study concludes that effective personnel performance contributes to favorable public service experiences and supports the development of a Service Improvement Plan. Recommended actions include customer service training, regular performance feedback, simplified service guidelines, real-time client feedback systems, and workflow review in Administrative Services. The study aligns with SDG 16 on Peace, Justice, and Strong Institutions and SDG 11 on Sustainable Cities and Communities by strengthening accountability, responsiveness, and citizen-centered local governance. Its sustainability impact lies in improving institutional, governance, and community sustainability through evidence-based service improvement and stronger alignment between internal performance systems and public satisfaction.
Keywords: Administrative Services; Citizen Satisfaction; Essential Services Delivery; Individual Performance Commitment and Review; Local Government Unit; Performance Management; Service Improvement Plan; Strategic Performance Management System